Peningkatan kemampuan pemecahan masalah matematis siswa kelas VII menggunakan model problem-based learning berbantuan Visual Basic for Applications Excel (VBA) - Fitri Nurul Aeni; Afrilianto, M.; Maya, Rippi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
The aim of this study is to evaluate the enhancement of mathematical problem-solving abilities among Grade VII Junior High School students using two different instructional models: the Visual Basic for Applications Excel (VBA) Assisted Problem-Based Learning Model and the scientific learning model. The research employs an experimental approach with a pretest-posttest control group design involving two groups: an experimental class and a control class. The entire 7th-grade population of SMP Negeri 3 Lembang participated in the study, with Class VII-D serving as the experimental group and Class VII-E as the control group. Data on mathematical problem-solving abilities were collected through pretest and posttest assessments. Data analysis was conducted using Microsoft Excel and SPSS 29. The findings indicate that students in the experimental group, who were taught using the Problem-Based Learning Model assisted by Visual Basic for Applications Excel (VBA), demonstrated greater improvement in their mathematical problem-solving skills compared to those taught using the scientific learning model.